2022
DOI: 10.3389/fnagi.2022.806439
|View full text |Cite
|
Sign up to set email alerts
|

Working-Memory, Alpha-Theta Oscillations and Musical Training in Older Age: Research Perspectives for Speech-on-speech Perception

Abstract: During the normal course of aging, perception of speech-on-speech or “cocktail party” speech and use of working memory (WM) abilities change. Musical training, which is a complex activity that integrates multiple sensory modalities and higher-order cognitive functions, reportedly benefits both WM performance and speech-on-speech perception in older adults. This mini-review explores the relationship between musical training, WM and speech-on-speech perception in older age (> 65 years) through the lens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…These explicit functions may depend on several inference-making operations within WM but also include several interactions with SLTM and Episodic Long-Term Memory (ELTM), hence taking a relatively longer time than effortless implicit processing. The implicit processes typically operate on a millisecond scale, and the explicit processes may take seconds ( Stenfelt and Rönnberg, 2009 ), and recent evidence suggests that different brain oscillations can dissociate the two (e.g., Gray et al, 2022 ). There will always be a ratio between the two, which is assumed to vary dynamically from moment to moment due to turn-taking and interlocutor responses in a conversation ( Rönnberg et al, 2019 ).…”
Section: The Elu Model Takes Shapementioning
confidence: 99%
See 2 more Smart Citations
“…These explicit functions may depend on several inference-making operations within WM but also include several interactions with SLTM and Episodic Long-Term Memory (ELTM), hence taking a relatively longer time than effortless implicit processing. The implicit processes typically operate on a millisecond scale, and the explicit processes may take seconds ( Stenfelt and Rönnberg, 2009 ), and recent evidence suggests that different brain oscillations can dissociate the two (e.g., Gray et al, 2022 ). There will always be a ratio between the two, which is assumed to vary dynamically from moment to moment due to turn-taking and interlocutor responses in a conversation ( Rönnberg et al, 2019 ).…”
Section: The Elu Model Takes Shapementioning
confidence: 99%
“…The explicit postdiction process may take seconds, while the prediction process is on the msec scale. The neural mechanism diverges between them: while the postdiction process is proposed to relate to theta-activity, the prediction process is proposed to relate to alpha-activity ( Gray et al, 2022 ). Typically, the postdiction process becomes more explicit and slower the neural process (i.e., probably related to enhanced theta activity), whereas the prediction processes are more implicit and probably related to faster neural activity, such as decreased alpha activity ( Gray et al, 2022 ) or beta activity ( Signoret et al, 2013 ).…”
Section: The Elu Model Takes Shapementioning
confidence: 99%
See 1 more Smart Citation
“…Gray et al [ 69 ] concluded in a mini-review that the characteristics of musical training as an integration of multiple sensory modalities and higher-order cognitive functions benefitted both WM performance and SIN perception in older adults. Just recently, Giallini et al [ 70 ] confirmed a significant link between attention, cognition, and WM capacity in CI users.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillations in different frequency bands could reflect different cognitive processed. For example, the alpha oscillations, which are supposed to be the most prominent oscillatory activity observed in scalp EEG recordings, can reflect the brain's cognitive performance such as working memory and the like (Grandy et al 2013;Bönstrup et al 2015;Gray et al 2022;Shah-Basak et al 2019;Doesburg et al 2011;Tian et al 2021). Haegens et al found a positive correlation between alpha oscillations for working memory (Haegens et al 2010), and Ouyang et al showed that power of alpha oscillations, especially in the rest state, is appeared to predict the cognitive speed (Ouyang et al 2020).…”
Section: Introductionmentioning
confidence: 99%